Pentru o relectură a romanelor ideologice eliadiene - Ștefan Firică (Revista de Istorie și Teorie Literară)
Undoubtedly, the boldest literary project of Mircea Eliade’s youth is the trilogy comprised of Întoarcerea din rai (1934 – “Return from Heaven”), Huliganii (1935 – “The Hooligans”) Viață nouă (“New Life”). Caught up in many other projects, whether scientific, cultural, or political, the author finished and published only the first and the second volumes of the series, while the third one is only partially known, from the fragments published posthumously, as well as from the author’s notes in Jurnalul portughez (“The Portuguese Diary”) or in Memorii (“Memoirs”). This article advocates for reading the three novels as instantiations of the ideological / political fiction (or roman à thèse), as conceptualized in the American and European theories of the last decades. We will meet a literature questionable from the ideological viewpoint, but surely in pace with the new narrative moulds developed worldwide, in the 1930s–1940s. Though rarely recognized as such, Eliade is the first Romanian author of modern ideological fiction, akin to the various versions of Existentialism which were, then, just taking off in Europe.